2002
DOI: 10.1096/fj.02-0223fje
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of nuclear factor‐κB and stress‐activated protein kinases in steroid unresponsiveness

Abstract: Glucocorticoid resistance is a serious clinical problem in chronic inflammatory diseases, because many patients with rheumatoid arthritis, asthma, or Crohn's disease fail to respond to steroid treatment. The molecular mechanisms underlying this unresponsiveness, however, are completely unknown. The effects of steroids are largely mediated by the interference of the glucocorticoid receptor (GR) with proinflammatory transcription factors. In the present study, we therefore investigated the activation of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 55 publications
1
64
0
2
Order By: Relevance
“…Consistent with these mechanistic proposals is the observation that corticosteroid-resistant asthmatics exhibit increased levels of JNK signalling pathway proteins and heightened JNK activity [60]. A similar observation has been made in patients with Crohn's disease [61]. Whether or not JNK inhibitors represent an alternative therapy for this difficult-to-treat group of patients remains to be seen.…”
Section: C-jun N-terminal Kinase Inhibitors and Glucocorticoidsmentioning
confidence: 64%
“…Consistent with these mechanistic proposals is the observation that corticosteroid-resistant asthmatics exhibit increased levels of JNK signalling pathway proteins and heightened JNK activity [60]. A similar observation has been made in patients with Crohn's disease [61]. Whether or not JNK inhibitors represent an alternative therapy for this difficult-to-treat group of patients remains to be seen.…”
Section: C-jun N-terminal Kinase Inhibitors and Glucocorticoidsmentioning
confidence: 64%
“…These findings validated the results from in-vitro cell culture studies [14] . Interestingly, increased JNK activation has also been shown in steroidresistant patients [15] . The significance of this finding is currently unclear.…”
Section: Role Of Jnk In Ibdmentioning
confidence: 95%
“…However, over 60% of steroid-resistant patients had a different staining pattern with active NF-B predominantly localized in epithelial cells. The same investigators subsequently showed that while the activation of AP-1 and the upstream kinases p38 and c-Jun N-terminal kinase (JNK) in steroid-sensitive patients with CD was mainly found in lamina propria macrophages, steroid-resistant patients revealed activation of all these mediators mostly in epithelial cells (Bantel et al 2002). The functional interference of these proinflammatory mediators with the glucocorticoid response was supported by reporter gene assays with expression of NF-B, JNK and p38 all inhibiting the activity of GR .…”
Section: Inflammation Nf-b and Glucocorticoid Resistancementioning
confidence: 99%